2011
DOI: 10.1016/j.amjmed.2010.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Using Hemoglobin A1C for Diagnosing Diabetes Mellitus

Abstract: Until 2010 the diagnosis of diabetes mellitus was based solely on glucose concentration, but American Diabetes Association (ADA) recommendations now include a new criterion: hemoglobin A1C ≥6.5%. Because this change may have significant implications for diabetes diagnosis, we conducted a comprehensive literature review including peer-reviewed articles not referenced in the ADA report.We conclude that A1C and plasma glucose tests are frequently discordant for diagnosing diabetes. A1C ≥6.5% identifies fewer indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 43 publications
(44 reference statements)
1
68
1
3
Order By: Relevance
“…Compared with plasma glucose, HbA1c is more reproducible, provides a better reflection of chronic glucose exposure and correlates well with diabetes-related complications [12][13][14][15]. Although the role of HbA1c as a diagnostic indicator was recognized, more longitudinal epidemiological studies have reported that demographic and ethnic factors may contribute to complications in using HbA1c for the diagnosis of diabetes, and the optimal diagnostic HbA1c cutoff of is debated and varies due to genetic and biological variations [16][17][18].…”
Section: Introductionmentioning
confidence: 97%
“…Compared with plasma glucose, HbA1c is more reproducible, provides a better reflection of chronic glucose exposure and correlates well with diabetes-related complications [12][13][14][15]. Although the role of HbA1c as a diagnostic indicator was recognized, more longitudinal epidemiological studies have reported that demographic and ethnic factors may contribute to complications in using HbA1c for the diagnosis of diabetes, and the optimal diagnostic HbA1c cutoff of is debated and varies due to genetic and biological variations [16][17][18].…”
Section: Introductionmentioning
confidence: 97%
“…Glycosylated hemoglobin A (HbA1c) is an index of blood glucose control, and it reflects the average blood glucose level for 2 to 3 months [910]. Normal HbA1c is below 6%, but it exceeds 6% in diabetes and can increase up to 10%–12% [11].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is not perfect concordance between results using the HbA 1c method and the FPG and 2-h PG tests. On the basis of a recent comprehensive literature review, it was concluded that HbA 1c ‡ 6.5% identifies fewer individuals with diabetes than glucose-based criteria [23]. HbA 1c has lower sensitivity, and it may inaccurately reflect glycaemia in the presence of certain anaemias and haemoglobinopathies [16].…”
Section: Markers Of Hyperglycaemia: Glucose Levels and Hba 1cmentioning
confidence: 99%